PENGARUH GAYA KEPEMIMPINAN SERVANT LEADERSHIP, DISIPLIN KERJA, DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. TRISAKTI SUMBER KARYA - Sihombing, Jonmaianto (ADAI Kepri, 2025)
PT. Trisakti Sumber Karya, a shipping subcontractor company established in 2019, has experienced a significant decline in employee productivity in recent years. This problem is related to the lack of functioning of the servant leadership role, motivation, training, and disharmonious communication, which contribute to the decline in employee performance. This study aims to (1) Analyze the partial effect of servant leadership style, work discipline, and job training on job satisfaction; (2) Analyze the partial effect of servant leadership style, work discipline, and job training on employee performance; (3) Examine the effect of job satisfaction on employee performance; (4) Analyze the effect of servant leadership style on employee performance through job satisfaction as an intervening variable; (5) Analyze the effect of work discipline on employee performance through job satisfaction as an intervening variable; and (6) Analyze the effect of job training on employee performance through job satisfaction as an intervening variable. This study uses a mixed methods method that combines qualitative and quantitative research. The study population involved 155 permanent employees of PT. Trisakti Sumber Karya, with a saturated sample covering the entire population. The data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to test the empirical model. This study concluded that all variables studied, namely servant leadership style, work discipline, and job training have a positive and significant effect on employee job satisfaction and performance at PT. Trisakti Sumber Karya. Work motivation plays an important role in improving employee performance. Servant leadership style and work discipline have a significant effect on employee performance through job satisfaction, while job training does not show a significant mediation effect. The implications of the results of this study are the importance of improving servant leadership style and work discipline and re-evaluating training strategies to improve employee performance more effectively.